Pengembangan Media Pembelajaran BETAMATH untuk Meningkatkan Pemahaman Siswa pada Materi Barisan dan Deret Aritmetika - Sriyanti, Linda; Rosyadi, Rosyadi; Taufan, Mochammad (Lembaga Intelektual Muda (LIM) Maluku, 2025)
The limited student understanding of arithmetic sequences and series, along with the minimal use of interactive Android-based learning media, served as the foundation for this study. The main objective of this research was to develop and evaluate the effectiveness of an Android-based learning application called BETAMATH in enhancing students' comprehension of the topic. This study employed a Research and Development (R&D) approach, using the 4D development model, which includes the stages of Define, Design, Develop, and Disseminate. The developed product was validated by subject matter experts, media specialists, and pedagogical experts, and was tested on tenth-grade students. Validation results indicated that BETAMATH is suitable for use in the classroom. Practicality testing revealed that the application is easy to use, based on student feedback and teacher observations. The effectiveness of the media was confirmed by a significant improvement in students' understanding, as shown by pretest and posttest results. Therefore, BETAMATH is considered valid, practical, and effective for improving student understanding of arithmetic sequences and series, and holds promise as an innovative alternative to support mathematics instruction in schools.